EXPLORING CONSUMER INTEREST, PRICE, AND PERCEPTION IN COFFEE PURCHASING DECISIONS AT BELIKOPI SIDOARJO - Yunita Wulandari; Mochamad Rizal Yulianto; Rizky Eka Febriansah (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2026)
This study was conducted to analyze the effect of purchase interest, price, and consumer perception on purchasing decisions at Kedai Belikopi Sidoarjo. The research method used was a quantitative approach with the help of Tolls SmartPLS version 3.29. Data collection was carried out by distributing questionnaires to Kedai Belikopi consumers, with a total of 96 respondents. From the test results, it can be seen that purchase interest has a positive and significant effect on purchasing decisions, with a T-count > the T table value of 1.98 and 4.700, and a P-Value of 0.00 below 0.05. Price has a positive and significant effect on purchasing decisions with a T-Statistic value of 2.559 and a P-Value of 0.011. Consumer perception does not affect purchasing decisions with a T-statistic value of 0.059 and a P-value of 0.953.